Depression is associated with worse outcomes among women undergoing breast reconstruction following mastectomy. Issue 8 (August 2019) - Drinane, James J.; Pham, Thuy-Huong; Schalet, Grant; Rezak, Kristen
Summary: Background: The causes of depression after breast reconstruction include worse outcomes, longer recovery times, and, sometimes, additional operations. Despite a plethora of data examining the effect of depression after breast reconstruction, there is little information to assess if concurrent depression affects patient outcomes in a similar manner. Thus, we sought to answer this question: Do depressed women undergoing breast reconstruction have worse outcomes? Methods: The United States National Inpatient Sample was queried during 2010–2013 for all patients undergoing breast reconstruction after mastectomy. Patients with a diagnosis of depression at the time of breast reconstruction were compared to those who did not have depression at the time of breast reconstruction; patients who had any of the corresponding ICD-9 procedure codes for breast reconstruction and the single diagnostic code for depression included in their electronic medical record were included in the database sample. Significance testing and risk-adjusted multivariate logistic regression were performed with SPSS. Results: A total of 175, 508 patients were included in this study, of which 35, 473 had depression at the time of breast reconstruction and 140, 035 did not. Depression was associated with an increased age, length of stay, greater cost of care, more comorbidities, and higher incidence of pulmonary, hematologic, gastrointestinal, infectious, wound, and venous thromboembolic complications, p <0.05. Pulmonary, genitourinary, and hematologic complications, infection, VTE, wound, and transfusion were associated with depression when a multivariate risk-adjusted regression was performed. Conclusion: A co-morbid diagnosis at the time of breast reconstruction should prompt the breast reconstruction team to ensure that depressed patients have their depression managed and all co-morbidities optimized and treated prior to undergoing breast reconstruction to ensure optimal patient outcomes.